Contribution to the phytosociological knowledge of rocky coastline of Corsica: description of five new plant associations - Bioret, Frédéric; Delbosc, Pauline; Panaïotis, Christophe (Lazaroa, 2017)
In this article the authors study a few Corsican rocky coasts plant communities, within the framework of the development of the Prodrome vegetation of Corsica. This work is based on the analysis of 51 unpublished phytosociological relevés and their comparison with previous historical data. Five new plant associations and subassociations belonging to Saginetea maritimae (Catapodio marini-Hymenolobetum revelierii and Catapodio marini-Centaurietum tenuiflori), Crithmo maritimi-Limonietea (Loto cytisoidis-Juncetum acuti), Artemisietea vulgaris (Loto cytisoidis-Dactylidetum hispanicae crithmetosum maritime) and Helichryso italici-Crucianelletea maritimae (Helichryso italici-Thymelaeetum tartonrairae) are described on the coastal cliffs of Corsica. Their synecological and synfloristic characteristics are presented together to other environmental features.